Metodologia de otimização de lentes para lâmpadas de LED - Barbosa, José Luiz Ferraz (2013)
The purpose of this work is to present a methodology for optimizing the geometry of the Light Emitting Diode (LED) secondary lens, in non-imaging applications, which focuses on the distribution of illuminance on a target plane. The simulation of Ray Tracing is produced by stochastic method and the optimization process based on heuristic search interacts with Ray Tracing to nd the optimized parameters of the LED secondary lens geometry.